2009
DOI: 10.20506/rst.28.1.1872
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of birds other than chickens and turkeys against avian influenza

Abstract: Most avian influenza (AI) vaccination and field studies have focused on chickens and turkeys because of their high death rates and the large amounts of highly pathogenic avian influenza (HPAI) virus that they excrete into the environment when infected. Data on vaccination of other species against HPAI remain limited. An increasing number of studies have been conducted to test the efficacy of inactivated vaccines in ducks and geese since it became clear that these species are a source of HPAI H5N1. One problem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Following vaccination with an inactivated H5N2 vaccine in free-range domestic ducks, sera were collected in flocks where unvaccinated sentinel birds had remained negative and were tested against the vaccinal antigen: HI titres ranged between 0 and 9 log 2 with a mean titre of 6 log 2 [28]. Other experimental studies have shown that vaccination against influenza in ducks with inactivated vaccines eventually requires higher antigen doses and multiple injections to be immunogenic and protective [29]. Depending on the type of vaccine used (inactivated or recombinant vector vaccine), experimental post-vaccination mean HI antibody titres against an antigen homologous to the vaccine usually remain low in Muscovy ducks, ranging from < 2 to 5.4 log 2 following a single injection [30-32].…”
Section: Dedicationmentioning
confidence: 99%
“…Following vaccination with an inactivated H5N2 vaccine in free-range domestic ducks, sera were collected in flocks where unvaccinated sentinel birds had remained negative and were tested against the vaccinal antigen: HI titres ranged between 0 and 9 log 2 with a mean titre of 6 log 2 [28]. Other experimental studies have shown that vaccination against influenza in ducks with inactivated vaccines eventually requires higher antigen doses and multiple injections to be immunogenic and protective [29]. Depending on the type of vaccine used (inactivated or recombinant vector vaccine), experimental post-vaccination mean HI antibody titres against an antigen homologous to the vaccine usually remain low in Muscovy ducks, ranging from < 2 to 5.4 log 2 following a single injection [30-32].…”
Section: Dedicationmentioning
confidence: 99%
“…The vaccination strategy should be carried out only in combination with biosecurity measures [ 21 – 23 ]. In the EU, commercial inactivated AI vaccines were licensed for use only in chickens and Pekin ducks, but they were also shown to be effective in other bird species [ 24 26 ]. It should be noted that only individual species of wild birds kept in captivity can be considered for AI vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…, ducks, geese, turkeys), zoo and/or exotic birds even within the same species ( i.e. , Muscovy vs. Pekin ducks) respond differently to vaccination which have not yet been fully investigated compared to chickens [35,36,37,38,39,40,41,42]. (9) Concomitant or prior infection with immunosuppressive pathogens or ingestion of mycotoxins can inhibit the immune response of AIV‑vaccinated birds [43,44,45,46].…”
Section: Introductionmentioning
confidence: 99%